2015
DOI: 10.1097/sle.0000000000000169
|View full text |Cite
|
Sign up to set email alerts
|

Economic Implications of Providing Emergency Cholecystectomy for All Patients With Biliary Pathology

Abstract: ALC is cost-effective and safe. It can be offered to all patients with biliary pathology provided they are fit enough for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The principal studies comparing index admission and elective cholecystectomy in patients admitted with biliary pathology do not acknowledge readmission morbidity before the operation and its impact on overall outcome [10][11][12][13][14][15][16][17][18]. This study demonstrates that the morbidity associated with readmission in BC patients is more severe than the difference in morbidity between index and elective cholecystectomy and cannot be disregarded.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The principal studies comparing index admission and elective cholecystectomy in patients admitted with biliary pathology do not acknowledge readmission morbidity before the operation and its impact on overall outcome [10][11][12][13][14][15][16][17][18]. This study demonstrates that the morbidity associated with readmission in BC patients is more severe than the difference in morbidity between index and elective cholecystectomy and cannot be disregarded.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, index admission surgery must be advocated as a cost-effective strategy for BC patients as this will reduce readmissions, overall morbidity and waiting times. This issue is ever more pertinent in the light of the COVID-19 pandemic which has resulted in increasing waiting list times and the further exposure to the risk of readmission [18,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 A review of 84 patients over a 12-month period from a single centre in the UK identified savings of £695 918 through implementation of early cholecystectomy. 27 Data from the United States show that patients presenting to ED with acute biliary pain and then discharged on a pathway for elective cholecystectomy have a 20% chance of representing within 30 days. What is also not captured is the rate of presentations to general practitioners with biliary type pain and the time and resources lost to the community by these visits.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy undertaken during the index admission is the standard of care for patients with acute cholecystitis and also for those with mild or moderate acute biliary pancreatitis (1)(2)(3). Index-admission management of symptomatic gallstone disease prevents recurrent biliary events and reduces healthcare costs (4,5). For such a strategy to be feasible, the necessary surgical expertise must be available to provide this level of care.…”
Section: Introductionmentioning
confidence: 99%